A COMPREHENSIVE SPECTRAL ANALYSIS OF THE X-RAY PULSAR 4U 1907+09 FROM TWO OBSERVATIONS WITH THE SUZAKU X-RAY OBSERVATORY - Rivers, Elizabeth; Markowitz, Alex; Pottschmidt, Katja; Roth, Stefanie; Barragan, Laura; Fürst, Felix; Suchy, Slawomir; Kreykenbohm, Ingo; Wilms, Jörn; Rothschild, Richard (Astrophysical Journal, 2010)
We present results from two observations of the wind-accreting X-ray pulsar 4U 1907+09 using the Suzaku Observatory. The broadband time-averaged spectrum allows us to examine the continuum emission of the source and the cyclotron resonance scattering feature at similar to 19 keV. Additionally, using the narrow CCD response of Suzaku near 6 keV allows us to study in detail the Fe K bandpass and to quantify the Fe K beta line for this source for the first time. The source is absorbed by fully covering material along the line of sight with a column density of N-II similar to 2 x 10(22) cm(-2), consistent with a wind-accreting geometry, and a high Fe abundance (similar to 3-4 times solar). Time-and phase-resolved analyses allow us to study variations in the source spectrum. In particular, dips found in the 2006 observation which are consistent with earlier observations occur in the hard X-ray bandpass, implying a variation of the whole continuum rather than occultation by intervening material, while a dip near the end of the 2007 observation occurs mainly in the lower energies implying an increase in N-H along the line of sight, perhaps indicating clumpiness in the stellar wind.
Keywords: pulsars: individual (4U 1907+09); stars: magnetic field; X-rays: binaries; X-rays: stars